Nitrogen Mineralization and Nitrification in Two Soils with Different pH Levels - Bergamasco, Marina Ali Mere [UNESP]; Braos, Lucas Boscov [UNESP]; Guidini Lopes, Ivã [UNESP]; Cruz, Mara Cristina Pessôa [UNESP] (Taylor & Francis, 2019)
Soil pH is one of the properties that mostly influences nitrification rates, and can be used as a tool for controlling this process, seen that depending on its extent it may lead to nitrogen (N) losses and subsequent contaminations. The aims of this study were to evaluate mineralization and nitrification of two soils at different pH levels. The experimental design was factorial with two factors and three replicates, with the first factor referring to two samples of red latosols, one eutrophic (LV1) and the other dystrophic (LV2), and the second factor was soil’s pH, at six levels: 4.0, 4.5, 5.0, 5.5, 6.0, and 6.5. Samples were incubated for 70 days in laboratory conditions. Both nitrate (N-NO3) and mineral N contents were determined and adjusted to growth models. The eutrophic soil presented higher mineral N and N-NO3, and the increase of pH levels led to increases of both inorganic N and N-NO3contents. Increases in pH levels caused N-NO3levels to increase in both soils, however this occurrence happened because it increased the amount of mineralized N in the soil, seen that in all pH ranges in both soils practically all mineral N was in the form of N-NO3.
Keywords: Nitrification; nitrogen mineralization; pH; soil acidity